2016
DOI: 10.2174/1871527315666160202124518
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on the dynamic association between oxidative stress and neurodegenerative disorders

Abstract: Free radicals are generated as byproduct of our body metabolism, and their adverse effect on normal functioning of our body is prevented by body's own antioxidant machinery. Any perturbation in the defense mechanism of antioxidants inside body, its abnormal production or its induction from environment to our body lead to serious threats and is responsible for the development of various neurodegenerative disorders (NDDs). Perturbed antioxidants result in sensory and functional impairments in neuronal cells, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…These free radicals harm neuronal mitochondria and challenge neuronal proteostasis and redox equilibria. Once a certain threshold of radical-mediated damage is reached, neurodegeneration is observed (Chen et al 2015 ; Khan et al 2016 ). In addition, activated glial cells can alter the integrity of the blood–brain barrier (BBB) and hence allow an infiltration of peripheral immune cells into the CNS (Lopez-Ramirez et al 2014 ).…”
Section: Key Event Relationships (Kers)mentioning
confidence: 99%
“…These free radicals harm neuronal mitochondria and challenge neuronal proteostasis and redox equilibria. Once a certain threshold of radical-mediated damage is reached, neurodegeneration is observed (Chen et al 2015 ; Khan et al 2016 ). In addition, activated glial cells can alter the integrity of the blood–brain barrier (BBB) and hence allow an infiltration of peripheral immune cells into the CNS (Lopez-Ramirez et al 2014 ).…”
Section: Key Event Relationships (Kers)mentioning
confidence: 99%
“…Then again, another perspective proposes a “two hit hypothesis” in AD, whereby a first hit of mitogenic signaling dysregulation induces CCE causing a “mitotic steady state” that is not sufficient to cause cell death. However, this comes at the expense of accumulating more insults whereby a second hit such as of oxidative stress then triggers neuronal degeneration (Zhu et al, 2007 ; Aliev et al, 2014 ; Khan et al, 2016 ). Both events are necessary and sufficient to cause the disease and may be common to other neurodegenerative diseases (Figure 3 ).…”
Section: Cell Cycle Control In the Adult Svz-ob Olfactory Dysfunctiomentioning
confidence: 99%
“…A large body of evidence has suggested that higher level of markers of oxidative stress including protein nitrotyrosine, carbonyls in proteins, lipid oxidation products and oxidized DNA bases exist in the brains of AD (Aslan and Ozben, 2004;Korolainen et al, 2006) and PD patients (Sanders and Greenamyre, 2013). It is well known that oxidative stress is involved in the pathogenesis of neurodegenerative disorders (Khan et al, 2016). In the pathological process, ROS attack neurons and glial cells, contributing to DNA injury, proteins misfolding and aggregation, inflammation, tissue damage and subsequent cellular apoptosis, which are directly or indirectly linked to neuronal cell death.…”
Section: Antioxidant Properties Of Baicaleinmentioning
confidence: 99%